Laboratory Findings, Medical Imaging, and Clinical Outcome in Children with Cerebral Sinus Venous Thrombosis - Glonnegger, Hannah; Glatthaar, Nicole; Eckenweiler, Matthias; Barth, Michael; Uhl, Markus; Büchsel, Martin; Zieger, Barbara (Hämostaseologie, 2022)
Introduction Cerebral sinus venous thrombosis (CSVT) is a rare disease, especially in children. Therefore, thrombophilia markers, risk factors, treatment strategy, and MRI, as well as clinical outcome need further investigation to support future diagnostic and therapeutic guidelines for children.Methods We retrospectively identified all children with CSVT treated in our center between January 1, 2000, and December 31, 2015. Risk factors and laboratory findings were investigated. Furthermore, outcome and treatment satisfaction were evaluated using magnetic resonance imaging (MRI) analyses and a modified questionnaire.Results All 43 patients, who agreed to participate, were treated with therapeutic levels of heparin; 86% of children had an increased risk for thromboembolic events upon onset of CSVT (acute disease: 58.1%, perinatal risk factors: 9.3%, medical intervention/immobility: 14%, chronic disease: 16.3%). Thrombophilia markers showed positive results (e.g., reduced values for protein C/S, factor-V–Leiden mutation) in 58% of children at the time of CSVT diagnosis but dropping to 20.9% over the course of the disease. Forty-two of 43 patients received MRI follow-ups and the outcome showed complete recanalization in 69% of the patients and partial recanalization in 31%. At the onset of CSVT, 88% of patients reported restrictions in everyday life due to CSVT; at follow-up this percentage declined to 18%. Satisfaction with the outcome among parents/patients according to the questionnaire was high with 1.7 (German school grades from 1 to 6).Conclusions All 42 children with MRI follow-up demonstrated complete or partial recanalization under anticoagulation. This positive result underlines the need for future studies on anticoagulation to optimize therapy regimens of pediatric CSVT.
Keywords: cerebral sinus venous thrombosis; anticoagulation; prothrombotic risk marker; outcome